Design and fabrication of mechanical tool for planting bed preparation - Mas’aud, Nurul Hanna; Abdul Malik, Norjasween; Jamaluddin, Luqman Nul Hakim (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
In line with Sustainable Development Goal 2 (Zero Hunger), one of the activities is to achieve food security through sustainable agriculture. To get a healthy and strong plants, a proper plant bed preparation is required. Where soil is the primary source of water and nutrients for plant. As for now, the bed preparation by small farmers is mostly done by traditional method which led to several health problems such as back pain and time consuming. Therefore, the aim of this project is to design and fabricate the mechanical tool for planting bed preparation. As compared with the existing product the major concern is regarding the cost. Instead of using motorized powered, this product introduced mechanical mechanism to move. It is expected that the users can construct the plant bed in standing position to push the cart and able to complete the process in large area within a short time. According to the analysis during testing, it is shown that the time taken is reduced from 270 seconds to 40 seconds to complete one plant bed with 1.5m length. It is about 85% time reduction. As a result, using this product save a lot of time and it might help in avoiding back pain to the farmers. In conclusion, this product may give a big impact to the farmers and encourage them to plant more vegetables to sustain food supply and at the end, creating a world free of hunger.